Health-Related Quality of Life Among Patients With Peripheral Arterial Disease. (July 2014) - Maksimovic, Milos; Vlajinac, Hristina; Marinkovic, Jelena; Kocev, Nikola; Voskresenski, Tatjana; Radak, Djordje
We evaluated health-related quality of life (HRQoL) among patients with peripheral arterial disease (PAD) and compared the results with those of the general population. We also evaluated the possible association between some demographic and clinical characteristics of patients with PAD and HRQoL. A cross-sectional study involved 102 consecutive patients with verified PAD referred to the Dedinje Vascular Surgery Clinic in Belgrade. The HRQoL was measured using Medical Outcome Survey Short Form 36 (SF-36). Patients with PAD had significantly lower mean SF-36 scores for physical functioning, role-physical, bodily pain, social functioning, role-emotional, and mental health in comparison with the general population. The HRQoL was significantly more impaired in patients with severe PAD. Patients with PAD had a reduced HRQoL compared with the general population. The impact of PAD on HRQoL was independent of other factors related to both the disease and the HRQoL.